PASTEUR ROMANIA – AN EMBLEMATIC LANDMARK OF THE VETERINARY MEDICINE FOR OVER 120 YEARS - Victorita Burghelea (Medicamentul Veterinar, 2016)
It is presented Pasteur Institute from Bucharest - an emblematic landmark of the veterinary medicine after more than 120 years (article in Romanian)